Institutional constraints on 'nudge-style' risk rating systems: explaining why food hygiene barometers were rolled-out in the UK but abandoned in Germany. Issue 11 (2nd November 2021) - Self, David; Rothstein, Henry
Abstract: This article advances international comparative regulatory scholarship on the implementation of nudge-style risk rating systems that are used to empower the public to make 'right' choices for their health, safety or security and help shape regulatee behaviour. Little attention, however, has been paid to the policy question of the extent to which the international introduction of such approaches and the form that they take, is dependent on the institutional contexts of regulation in different countries. Drawing on 55 key informant interviews and extensive policy document analysis, we examine starkly contrasting attempts to introduce 'food hygiene barometers' in the UK and Germany, having been successfully introduced in the former, but abandoned in the latter. This outcome can partly be explained by the stronger sectoral organisation of food businesses and the number of policy veto points they can exploit in Germany compared to the UK. More significantly, however, the study identifies strong institutional contrasts between the two countries; both in the way they balance rights to consumer information, public health and economic activity as well as the extent to which ideas of consumer sovereignty can be instrumentalised for regulatory purposes. The article concludes by pointing to how the form, purposes or even the very possibility of nudge-style public policy interventions are likely to vary from country to country, depending on their fit with the conceits and character of nationally-specific regulatory philosophies, constitutional and legal norms, and juridical ideas about consumer sovereignty.